Privacy in the majesty of death… Preliminary reflections (Requiem, 2025)
Łódź University What Attitudes Toward the End of Earthly Existence Did Poles Exhibit During the Partition Era? The final journey, death, and mourning were issues that resonated particularly strongly during the period of national captivity. The deaths of heroes on the battlefield fighting for a free homeland, death as a punishment for participating in national movements, death far from home - in exile or deportation - and mourning in both individual and collective dimensions, including national mourning, were themes frequently evoked by contemporaries. These themes left a profound mark on the perception of the entire era. Despite the extensive knowledge of death as something grand, unjust, and a symbol of sacrifice for higher ideals, the issue of dying in a private context remains relatively unexplored. The cognitive perspective proposed in this volume aims to provide a scholarly reflection on the image of life’s end, the experience of agony, death, and mourning among representatives of various social strata; the place assigned to death in private life; the rituals surrounding the dying and forms of burial; the emotions associated with death; and, finally, the relationships between the living and the dead. Scholars from various disciplines - including historians, art historians, literary scholars, cultural historians, anthropologists of history, and museum professionals - have contributed to the discussion on individual and collective experiences of death in the 19th century.